The courier [videorecording (DVD)] - Cumberbatch, Benedict, 1976-; Niniże, Merab, 1965-; Brosnahan, Rachel; Buckley, Jessie, 1989- (Lionsgate, 2021)
The true story of a British businessman unwittingly recruited into one of the greatest international conflicts in history. Forming an unlikely partnership with a Soviet officer hoping to prevent a nuclear confrontation, the two men work together to provide the crucial intelligence used to defuse the Cuban Missile Crisis.